2013
DOI: 10.1073/pnas.1312848110
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of long-range temporal dependence in default mode and attention networks during deep sleep

Abstract: The integration of segregated brain functional modules is a prerequisite for conscious awareness during wakeful rest. Here, we test the hypothesis that temporal integration, measured as longterm memory in the history of neural activity, is another important quality underlying conscious awareness. For this aim, we study the temporal memory of blood oxygen level-dependent signals across the human nonrapid eye movement sleep cycle. Results reveal that this property gradually decreases from wakefulness to deep non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
200
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(231 citation statements)
references
References 57 publications
(65 reference statements)
27
200
0
4
Order By: Relevance
“…S5 A and B) (H awake = 0.772; H deep = 0.722; bootstrap analysis, P = 0.03), and marginally lower in moderate sedation than in awake (H moderate = 0.724; bootstrap analysis, P = 0.05) but did not differ significantly between sedation conditions (P > 0.1). The drop in H value indicates, in agreement with previous work on sleep (35) and anesthesia (36), that there is a breakdown of temporal integration in the sedated brain. To relate the fluctuations in H value over different sessions with fluctuations in brain states, we calculated for every session the mean similarity score index, or the average similarity to the anatomical connectivity matrix score across all brain states present in a single session.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…S5 A and B) (H awake = 0.772; H deep = 0.722; bootstrap analysis, P = 0.03), and marginally lower in moderate sedation than in awake (H moderate = 0.724; bootstrap analysis, P = 0.05) but did not differ significantly between sedation conditions (P > 0.1). The drop in H value indicates, in agreement with previous work on sleep (35) and anesthesia (36), that there is a breakdown of temporal integration in the sedated brain. To relate the fluctuations in H value over different sessions with fluctuations in brain states, we calculated for every session the mean similarity score index, or the average similarity to the anatomical connectivity matrix score across all brain states present in a single session.…”
Section: Resultssupporting
confidence: 90%
“…The latter observation is consistent with the literature on sleep (35) and anesthesia (36): a loss of consciousness is associated with a drop in H value toward 0.5, the value that arises when the dynamics of time series is close to white noise, lacking temporal memory. How could more stable brain states arise from noisier and increasingly memoryless time series?…”
Section: Discussionsupporting
confidence: 92%
“…Acquisition parameters and details for these data have been previously published (55). The fMRI was acquired using a 3T scanner (Siemens Trio) with optimized polysomnographic settings (1,505 vol of T2*-weighted echo planar images, repetition time/echo time = 2,080 ms/ 30 ms, matrix = 64 × 64, voxel size = 3 × 3 × 2 mm 3 , distance factor = 50%, field of view = 192 mm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Included are 70 epochs of wakefulness and 38 epochs of N3 sleep (SWS). Detailed sleep architectures of each participant have been previously published (55).…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that there is a reduction in functional integration in this state of consciousness. These results point to a general impairment of functional connectivity on the level of the thalamocortical system as a whole, possibly underlying the reduction of consciousness (Tagliazucchi et al, 2013a). A potential limitation of the studies discussed above is that they did not involve obtaining subject mentation reports in the sleep stages of interest.…”
Section: Global Cortical Connectivitymentioning
confidence: 99%